Maternal exposure to antibiotics and risk of atopic dermatitis in childhood: a systematic review and meta-analysis - Wan, Mengjie; Yang, Xiaoyang (Frontiers in Pediatrics, 2023)
Background: Although the association between maternal exposure to antibiotics and the risk of atopic dermatitis (AD) in childhood has been studied extensively, there still is a lack of clarity on the topic. The aim of this study was to summarize the published data and to examine if maternal exposure to antibiotics increases the risk of AD in childhood. Methods: Systematic search was performed in PubMed, Scopus, Web of Science, and Embase for all types of studies on the review subject independent of any language restrictions and published up to 28th December 2022. Data was analyzed using random-effects model and presented as pooled odds ratio (OR) with 95% confidence intervals (CI). Results: A total of 18 studies (5,354,282 mother-child pairs) were included. Maternal exposure to antibiotics was associated with an increased risk of AD in childhood (OR: 1.14 95% CI: 1.06, 1.22 I2=85% p=0.0003). The significance of the results was not affected by the location of the study (Asia or Europe). While subgroup analysis based on exposure assessment or diagnosis of AD demonstrated a tendency of increased risk of AD, the association was not statistically significant in multiple subgroups. Segregating data based on the timing of exposure did not affect the significance of the results for studies on all trimesters. However, there was no association between antibiotic exposure in the third trimester or just before delivery and the risk of childhood AD. Conclusion: The results of this meta-analysis suggest that maternal exposure to antibiotics may lead to a modestly increased risk of AD in offspring. The evidence is limited by high interstudy heterogeneity and bias in exposure and outcome assessment. Future studies are needed to explore if the timing of exposure, the dose, the number of prescriptions, and the type of antibiotic affect this association.